Factors Associated with Social C ปัจจัยการกลั่นแกล้งบนสังคมออนไลน์ของเยาวชนสามจังหวัดชายแดนภาคใต้ - Masamae, Abdunfatah (Al-HIKMAH Journal, 2021)
This research was a quantitative research which is aimed to study the frequency of social cyberbullying in several formats and to study the factors associated with the social cyberbullying. The population and sample size of this study was 240 persons of youths who lived in the three southernmost provinces of Thailand. Quota sampling was applied to select the sample size and questionnaire was used as a research tool. Descriptive analysis is applied to explore the frequency and percentage. Correlation and univariate analysis were tested by the Pearson chi-squared test. Separated dichotomous outcomes of logistic regression were modelled: youth who bullied other, youths who had been bullied by other, and both of youths who bullied other and had been bullied by other. The result found that 174 persons of youth (72.50%) bullied others, 122 persons of youth (50.83%) had been bullied by other, and 77 persons of youth (32.08%) had bullied other and had been bullied by other. Three models shared the common factor of causing to occur the cyberbullying was a factor of “forgetting to resign the social media after signing-on in the public computer”.